Production of microbial L-asparaginase - Batool, Tahira (2016)
This study aims at production of L-asparaginase by microbes using natural substrates (squid pen and Moringa oleifera seeds). Primarily 31 bacterial isolates and 4 fungi were screened for L-asparaginase production. Nutrient broth medium was used for bacterial isolates, while potato dextrose agar was used to grow fungi. Both squid pen and Moringa oleifera seeds were used as substrate in this study. The cell-free filtrate was obtained and used as enzyme. Protein content was assayed using Lowry method while enzyme activity was determined by Nessler’s reaction. Eight most potent bacterial isolates were selected for secondary screening and were grown in modified minimal salts 2X media without glucose. On the basis of results obtained during secondary screening, only two bacterial isolates A9 and E.coli ATCC 10536 were selected. All four fungi were also screened, and none of the fungi could show significant enzyme activity hence none of them was considered for further studies. Both A9 and E.coli ATCC 10536 were grown separately in the presence of squid pen or Moringa oleifera and process parameters were investigated for maximum L-asparaginase production by one factor at a time (OFAT) method. Highest enzyme activity (48.16IU/ml) was obtained with galactose (1% w/v), ammonium chloride (1% w/v), pH 7, temperature 37°C, inoculum size 12% v/v, substrate concentration 1% w/v and incubation period 6 days for A9MO. While, for A9SP all factors were same except starch (1% w/v) that was best carbon source. In the case of E.coli MO and E.coli SP, no external carbon source could enhance the activity. Other factors were similar to the A9MO and A9SP isolate except incubation period that was only three days in case of E.coli MO and pH that was recorded to be 6 and nine respectively. A9 and E.coli ATCC 10536 L-asparaginase was produced on a large scale (1.5L) and precipitated using ammonium sulfate. Subsequently, dialysis was performed and enzyme was freeze dried to carry out anticancer activity. Effect of various metal ions and EDTA was studied. Hg2+, Co2+, Ca2+, Cu2+, and Mg2+ reduced the enzyme activity while Na+ and K+ enhanced it. The activity of the partially purified enzyme was stable at a range of pH 3 to 10. 37ºC of incubation temperature was determined as optimum and enzyme was stable over a range of temperature (7, 25, 37, 40, 50 and 80 ºC). The anticancer activity was determined with different concentrations of L-asparaginase, tested on HeLa cancer cell line. The lower concentration (3.125 μg/mL) of E.coli MO enzyme inhibited the cell viability to 86.540 μg/mL, while at a concentration of 100 Μm, the viability of the HeLa cells decreased to 25.186% with an IC50 of 33.745μg/mL. The results obtained in the present study indicated that both Ecoli ATCC 10536 and A9 could be potential strains for maximum L-asparaginase production with Moringa olefiera and squid pen as substrates.